Stres Polisi: Menguji Peran Fleksibilitas Kognitif dan Dukungan Sosial - Kristianingsih, Sri Aryanti; Ambarwati, Krismi Diah; Pombadju, Vanda Leony Agnesila (Bulletin of Counseling and Psychotherapy, 2025)
Police are one of the professions that are at risk of experiencing high stress while carrying out their work. Stress can have a negative impact on a person so it is important to understand things that can affect stress, including cognitive flexibility and social support obtained from family and friends. The purpose of this study is to determine the role of cognitive flexibility and social support on police stress in Central Java Regional Police. The research subjects were 3292 police officers in the Central Java Regional Police. This research was conducted using a correlational quantitative approach. The research subjects were obtained through accidental sampling technique and 3292 research subjects were obtained. The research data collection instruments were the Depression Anxiety Stress Scale (DASS-21) to measure stress levels, the adapted Social Support Scale (SSS) to measure perceptions of social support and the Cognitive Flexibility Inventory to measure the level of cognitive flexibility. Regression analysis was used to test the hypotheses in this study. The results showed that flexibility of thinking, social support (family and friends) simultaneously had a very significant effect on police stress within the Central Java Police. It can be concluded that flexible thinking and perceptions of social support from family and friends play a role in police stress levels.